2016
DOI: 10.2174/1389202917666160202220238
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Seed Development: Fatty Acid and Phytohormone Metabolism and Their Interactions

Abstract: Vegetable oil utilization is determined by its fatty acid composition. In soybean and other grain crops, during the seed development oil accumulation is important trait for value in food or industrial applications. Seed development is relatively short and sensitive to unfavorable abiotic conditions. These stresses can lead to a numerous undesirable qualitative as well as quantitative changes in fatty acid production. Fatty acid manipulation which targets a higher content of a specific single fatty acid for foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 214 publications
(333 reference statements)
0
10
0
Order By: Relevance
“…The KEGG analysis of RNA-Seq data presented in this paper provides evidence for a significant change in the expression of hormone signal transduction pathway genes in peanut pods, especially those involved in auxin signal transduction pathways. Previous studies have also shown that the signal transduction of hormones is important in the maturation process, and that the two mechanisms have a very close relationship (Hands et al, 2016 ; Nguyen et al, 2016 ). Thus, to gain deep insights into the transcriptional regulation of hormone signal transduction genes during peanut pod development, genes involved in this process were studied at the three different developing stages in the two lines.…”
Section: Resultsmentioning
confidence: 97%
“…The KEGG analysis of RNA-Seq data presented in this paper provides evidence for a significant change in the expression of hormone signal transduction pathway genes in peanut pods, especially those involved in auxin signal transduction pathways. Previous studies have also shown that the signal transduction of hormones is important in the maturation process, and that the two mechanisms have a very close relationship (Hands et al, 2016 ; Nguyen et al, 2016 ). Thus, to gain deep insights into the transcriptional regulation of hormone signal transduction genes during peanut pod development, genes involved in this process were studied at the three different developing stages in the two lines.…”
Section: Resultsmentioning
confidence: 97%
“…Fatty acid content not only plays a key role in the quality of soybean oil but also impacts the development of soybean seeds (Haun et al, 2014;Nguyen, Kisiala, Andreas, Neil Emery, & Narine, 2016). At present, there have been many studies on QTLs related to soybean fatty acid content.…”
Section: Discussionmentioning
confidence: 99%
“…Among their multiple functions, CKs are a key drivers of seed yield (reviewed by Chen et al., 2020; Jameson & Song, 2016). In soybean, CKs are: involved in preventing flower abortion and in pod setting (Nonokawa et al., 2012); associated with seed development and fatty acid biosynthesis (Nguyen et al., 2016); and ultimately, responsible for seed yield (Kambhampati et al., 2017). Studies on genetic analysis of CKs aid greatly in the understanding of fundamentals of plant physiology and they help build genetic resources for high yielding crop breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…CK metabolites are strongly associated with the enhancement of soybean reproductive development. HPLC‐MS/MS based CK quantifications have clearly established their distinct correspondence with cell division, cell expansion, and dehydration during embryo development, seed protein and lipid accumulation, and in the DNA endoduplication (Kambhampati et al., 2017; Nguyen et al., 2016). Therefore, the present study surveyed the complete set of CKs during three reproductive stages that critically define pod and seed development and yield formation in soybean.…”
Section: Discussionmentioning
confidence: 99%